Utilization of the Goodnight Application as a Media for English Speaking Practice : Penelitian - Yugi Diraga Prawiyata; Lidya Marshanda; Deliana Putri (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Speaking is a productive skill involving the use of grammar, vocabulary, pronunciation, and intonation to express ideas orally. This study employs the Goodnight application as a medium for English speaking practice among fifth-semester English Education students. The research aims to explore students' perceptions of the application use and to describe its effectiveness in enhancing speaking ability and self-confidence. A qualitative descriptive method was applied, with data collected through open-ended questionnaires and analyzed via thematic analysis supplemented by data triangulation for validity. Findings reveal that the Goodnight app effectively reduces speaking anxiety while improving fluency, vocabulary, and responsiveness in English conversations, despite challenges such as initial limited vocabulary. This study underscores the role of interactive digital media in supporting authentic and contextual language learning.